The contribution of economic sectors towards economic growth in Malaysia / Aina Syafiqah Mohd Nazri - Mohd Nazri, Aina Syafiqah (2018)
The objective of this study to determine the relationship and the effect that influence of economic sector towards Gross Domestic Product (GDP) growth using the period year from 1987 to 2017. This study consists of five independent variables which are value added of manufacturing sector, value added of services sector, value added of agriculture sector, value added of construction sector and value added of mining sector. It is known that these variables are expected to have significant relationship to the dependent variable. The data has been analyses using Ordinary Least Square (OLS) model.